¿Qué es la criminología verde? - Ailén Jarque, Melisa (Archivos de criminología, seguridad privada y criminalística, 2021)
Green criminology is a tendency that has been aborded in United States and Europe, but in Lationamerica is a pendent. The search of new kinds of prevence of ambiental damage justified that criminologists extend their knowledge about criminals and treatement of victims, to the ambiental area. From the origins until the tematics that could be interest for the green criminology, this work try to create a new look about the environmental problems that we have been suffering for a long time.